Three new genera and ten new species of the subfamily Lecithocerinae (Lepidoptera, Lecithoceridae) from Cameroon, Africa, based on material collected in 1913–18 - Park, Kyu-Tek (Zootaxa, 2018)
Based on material collected in Cameroon, Africa in 1913–18 and deposited in the Carnegie Museum of Natural History, Pittsburgh, USA, three new genera and 10 new species of Lecithocerinae (Lecithoderidae) are described and illustrated. The new genera are Paniculata gen. nov., Furcalis gen. nov., and Notioseus gen. nov. The new species are Homaloxestis rawlinsi sp. nov., Lecithocera afrotella sp. nov., L. dysmica sp. nov., L. cyclisca sp. nov., Paniculata weberi sp. nov., Notioseus cupripennis sp. nov., N. acidodes sp. nov., Furcalis efulenica sp. nov., F. triodonta sp. nov., and Lacuniola noda sp. nov. Adults and their labels, and the genitalia of all the species treated herein are illustrated.